Age-Dependent Activation and Neuronal Differentiation of Lgr5+ Basal Cells in Injured Olfactory Epithelium via Notch Signaling Pathway - Li, Xuewen; Tong, Meimei; Wang, Li; Qin, Yumei; Yu, Hongmeng; Yu, Yiqun (Frontiers in Aging Neuroscience, 2020)
Aging is an important factor affecting function of smell, leading to the degeneration of mature olfactory sensory neurons and inducing the occurrence of smell loss. The mammalian olfactory epithelium (OE) can regenerate when subjected to chemical assaults. However, this capacity is not limitless. Inactivation of globose basal cells and failure to generate sensory neurons are the main obstacles to prevent the OE regeneration. Here, we found the significant attenuation in mature sensory neuronal generation and apparent transcriptional alternation in the OE from aged mice compared to young ones. The recruitment of Leucine rich repeat containing G protein coupled receptor 5 (Lgr5) positive cells in injured OE was weakened in aged mice, and more Lgr5+ cells remained quiescence in aged OE post injury. Lineage traced progenies from Lgr5+ cells was significantly fewer in the OE with aging. Moreover, Notch activation enhanced the neuronal regeneration in aged OE, making the regenerative capacity of aged OE comparable to that of young animals after injury. The growth and morphology of three-dimensional (3D)-cultured organoids from the OE of young and aged mice varied and was modulated by small molecules regulating the Notch signaling pathway. Thus, we concluded that activation of Lgr5+ cells in injured OE was age-dependent and Notch activation could enhance the capacity of neuronal generation from Lgr5+ cells in aged OE after injury.